Cross-Border Electricity Cooperation in South Asia - Singh, Anoop (World Bank, Washington, DC, 2015)
South Asian countries, facing challenges in efficiently meeting growing electricity demand, can benefit from increased cross-border electricity cooperation and trade by harnessing complementarities in electricity demand patterns, diversity in resource endowments for power generation, and gains from larger market access. The region has witnessed slow progress in expanding regional electricity cooperation and trade, and undertaking needed domestic sector reforms. Although bilateral electricity sector cooperation in the region is increasing, broader regional cooperation and trade initiatives have lagged in the face of regional barriers and domestic sector inefficiencies. Deeper electricity market reforms are not a necessity for further development of cross-border electricity trade, but limited progress in overcoming regional and domestic barriers will limit the scope of the regional market and the benefits it can provide.